2012
DOI: 10.1021/jp306555j
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Nanoparticle-Decorated SiO2 Nanospheres Exhibiting Remarkable Plasmon-Mediated Photocatalytic Properties

Abstract: We demonstrated for the first time that Agnanoparticle-decorated SiO 2 nanospheres (NSs) may display noticeable photocatalytic activities upon surface plasmon resonance (SPR) excitation. The samples were prepared by reacting SiO 2 NSs with AgNO 3 in the seed-mediated growth process, from which the Ag particle size and decoration density can be readily controlled. The dependence of the SPR-mediated photocatalytic performance of Ag-decorated SiO 2 NSs on the Ag morphology was investigated and presented. The as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 39 publications
4
110
0
Order By: Relevance
“…Notably, no diffraction peaks corresponding to rGO or Ag were observed, owing to the low amount of rGO and the small size of the Ag nanoparticles. [17,46,47] The existence of Ag nanoparticles was evidenced by TEM and was also could further evidenced by X-ray photoelectron spectroscopy (XPS) measurements. The surface compositions and elemental chemical states of the TGA composite were characterized by using XPS.…”
Section: Characterization Of the As-prepared Samplesmentioning
confidence: 96%
“…Notably, no diffraction peaks corresponding to rGO or Ag were observed, owing to the low amount of rGO and the small size of the Ag nanoparticles. [17,46,47] The existence of Ag nanoparticles was evidenced by TEM and was also could further evidenced by X-ray photoelectron spectroscopy (XPS) measurements. The surface compositions and elemental chemical states of the TGA composite were characterized by using XPS.…”
Section: Characterization Of the As-prepared Samplesmentioning
confidence: 96%
“…For the HNTs sample, the observed peaks at 20.01, 24.79, and 29.98 can be indexed to the characteristic peaks of halloysite [39]. However, the two new peaks at 35.6˚and 43.2˚, which can be indexed as (311) and (400) [41], respectively. Moreover, no diffraction peaks corresponding to silver oxide were observed, which confirmed that only metallic Ag was formed by chemical reduction method.…”
Section: Xrd Analysismentioning
confidence: 95%
“…Scheme 1 Synthesis of microporous silica nanoparticles have been investigated for plasmon-mediated photocatalysis (Chen et al 2012). However, microporous SiO 2 /blue Ag composite nanostructures have not been reported to the best of our knowledge.…”
Section: Teosmentioning
confidence: 99%